Selected Topics on Managing Complexity and Information Systems Engineering: Editorial Introduction to Issue 8 of CSIMQ - Forbrig, Peter; Espana, Sergio; Ivanovic, Mirjana (Complex Systems Informatics and Modeling Quarterly, 2016)
Business process models greatly contribute to analyze and understand the activities of enterprises. However, it is still a challenge to cope with the complexity of systems specifications and their requirements. This issue of the journal of Complex Systems Informatics and Modeling (CSIMQ) presents papers that discuss topics on managing complexity and information systems engineering. The papers are extended versions of selected papers from the workshop on Continuous Requirements Engineering held at the requirements engineering conference REFSQ 2016 in Gothenburg, the workshop on Managed Complexity held at the business informatics conference BIR 2016 in Prague, and the CAiSE 2016 Forum held in Ljubljana.